Acquired Haemophilia: A Case Report and Literature Review - Regan, Caine; Gatnash, A. (Journal of Hematology and Oncology Research, 2026)
Acquired haemophilia (AHA) is a rare coagulation disorder secondary to autoantibodies against coagulation factor, most commonly factor VIII with potential for life threatening bleeding episodes. We report a case of an 88-year-old female presenting with frank haematuria three weeks after catheter insertion. Her background was of Alzheimer’s Dementia, Asthma and Bullous Pemphigoid for which she was on low dose maintenance prednisolone (5mg). Laboratory tests showed haemoglobin 98g/dl and partial thromboplastin time (PTT) of 60s, with corrected prothrombin time 52s. Fibrinogen 5.39. As such coagulation factors were tested which revealed factor VIII of 0%. Her case was complicated by urinary tract sepsis, as such she was treated with oral prednisolone 60mg without immunosuppressive agent usage. A pan-CT scan revealed likely mesothelioma for which she declined further investigation. This case report will describe a rare presentation of AHA associated with bullous pemphigoid and mesothelioma, complicated by infection and frailty.
Keywords: Acquired haemophilia; immunosuppressive agent; coagulation factor